Human Resource Management Practices in Supporting Sustainable Performance at PT Telkom Indonesia Tbk - Alifia Mukti, Nadyah; Kurniawati, Endah; Harianto, Kukuh (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to analyze human resource management (HRM) practices in supporting the sustainable performance of PT Telkom Indonesia Tbk. Using a descriptive qualitative approach, this study draws on data from the documentary analysis of PT Telkom Indonesia Tbk's 2024 Sustainability Report. The findings show that sustainable HRM at Telkom operates across four strategic pillars: inclusive recruitment, competency development, employee well-being, and an organizational culture based on the AKHLAK values. These practices improve human resource quality and influence innovation, productivity, and social inclusion. Therefore, companies need to systematically integrate HRM into corporate policies to support sustainable performance. Keywords: Human Resource Management, Sustainable Performance, Sustainability Report